Reciprocating Compressor Dynamics Modelling by a Bond Graph Approach - Ovy, Enaiyat Ghani; Sun, Qiao (Journal of Vibration Testing and System Dynamics, 2026)
This research is dedicated to developing an analytical physics-based model of a reciprocating compressor based on a bond graph approach. At first, a mathematical model is developed for one-cylinder reciprocating compressor based on multi-body dynamics, particularly considering planar motion of the rigid bodies using body fixed reference frames. All the dynamical equations of motions are represented and linked altogether by the bond graph that simulates a complete system model. The model has unique capability to show forces at various joints, which enhances our understanding of complex system behavior. Moreover, the consequences of changing coefficients of those forces are accentuated. The utility of the model in fault diagnosis and condition monitoring are emphasized by highlighting the effects of a crack in a joint and a dent on cylinder wall. Nonlinear differential equations extracted from bond graph model are solved efficiently using a MATLAB stiff solver. Responses of the model parts are analyzed later by force analysis along with a comparison with a previous research to examine model validity.